مؤتمر لوزان(مؤتمر تقسيم كوردستان)"دراسة جيوبولتيكية" - خورشيد, فؤاد حمة; طالب, جةزا توفيق (Sulaimani Journal for Humanities)
Lausanne Conference: A Conference that divided the Kurdish Homeland AGeopontical Study A Geopolitical Study This study deals with Laussanne Conference of 1922 according which the Kurdish origin homeland has divided to different regions. Signing (Modane ) cease-fire agreement between both Great Britain and Turkey, on Nov. 1922, had paved the way for settling all Suspendednt case including the so called ( Mosul Vilayet problem ). Laussane conference has turned a blind eye to the articles of the previous agreement known as ( Sever ) agreement which were in favor of Kurdish national interests. In Lossane conference that lasted more than a year , ( from 20, Nov.1922 to 31,Jan, 1923 ) both Great Britain and Turkish delegations exchanged their views on Mosul problem, explained their different , and even their allegation to annex Mosul vilayet to their territories . The tw sides expressed their claims on this region and both sides reiterated their rights in his prosperous their claims were based on : 1.Ethongraphic factors. 2.Ploitical reasons. 3.Historical rights. 4.Geographic and economic facts . 5.Military & Strategic factors. 6.Turkish National accord. In this study we tried to analyze the two sides claims and counter claims , we have also explained the Losanne conference & its defects, especially those articles which has connived Kurdish historical rights in their origin homeland , & also we foxed on those articles that paid no attention to the long standing Kurdish struggle for self-determination. And finally we underlined the impact of this agreement and its results on Kurdish modern history as a whole.